KAJIAN INTERAKSI DAN PERANAN MEDIA SOSIAL DALAM PEMBELAJARAN DARING MAHASISWA PADA ERA PANDEMI COVID-19 DI IAIN TULUNGAGUNG - Miftachul Hidayah; Soemedi Hadiyanto (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2021)
E-learning in the Covid-19 pandemic era caused limited social interaction and depended on social media literacy from providers and users in learning units, causing constraints on the quality and effectiveness of learning. The research objective was to examine social interactions and the role of social media in student e-learning during the Covid 19 pandemic at IAIN Tulungagung. Descriptive quantitative research methods. The population was 23,423 students, the sample was 3,483 students (14.87%). The data collection tool used a list of questions, the duration of data collection was 1 month April 2021. Data analysis included the calculation of means, percentages, presentation of graphs and tables with SPSS version 25.0 for windows. Result; learning at home, using a mobile internet connection and using the WhatsApp application and google classroom. Learning material innovation is needed so that learning is easily accessible from cellphones. E-learning limits socializing and reduces free time. Barriers to online lectures are mainly limited internet signal, then costs incurred, difficult material and a lot of assignments, 83.49% students that they disagreed with the statement that online lectures were cheap. Innovation and planning for interactive learning methods are needed so that students can interact actively and facilitate student access to the internet.